Emosi Remaja Kecanduan Game Online Mobile Legends - Ulfa Mulyani; Wahidah Fitriani (Program Studi Bimbingan dan Konseling, FKIP Universitas Pancasakti Tegal, 2022)
Teenagers' emotions that cannot be controlled when playing mobile legends online games that cause excessive reactions to those around them, for this reason the purpose of this research is to find out a picture of teenagers' emotions that have an impact on mobile legends online game addiction and to know the factors that cause addiction to mobile online games. legends. The research method used is descriptive qualitative research with data collection techniques through observation, interviews and documentation. The subjects of this study were teenagers aged 13 to 17 years, totaling 10 teenage subjects with active players in the mobile legend online game in Mandau, Duri, Riau. Data were analyzed descriptively. The implementation of this research starts from research design, data collection, data analysis and verifying the data found. The results of the research are from the emotions of teenagers who are addicted to the online game mobile legends which have unstable emotions, speak harshly, explosive emotions, fight, cannot communicate well, hit objects around, commit violence, make loud noises to people. around, excessive in attitude and upset to experience defeat. Factors affecting addiction to mobile legends online games are caused by internal factors of teenagers with a desire to play continuously and external factors from the environment of teenagers that influence teenagers to become addicted to online games mobile legends. It was concluded that the emotions of teenagers who were addicted to the mobile legends online game were not emotional, could not control their emotions and issued harsh sentences.